International Cooperation in Competition Law Matters A Closer Look at Trade Agreements - Godt, Anton (Universitätsverlag Göttingen, 2022)
The study outlines the status quo of international cooperation in competition law matters. This is done by examining, in chronological order, the various approaches of the many multi- and bi-lateral international agreements that have attempted to solve the problems of competition law (WTO, GATT, etc.). Subsequently, the focus of this thesis is on the analysis of bilateral trade agreements. Within the framework of this analysis, the potential of trade agreements for competition law cooperation is to be shown. For this reason, only those bilateral trade agreements are analyzed that deal with the topic of regulatory cooperation in competition law in specially provided competition chapters. In doing so, the different stages of cooperation will be analyzed along the different integration phases of any trade agreements. The highest form of trade agreement integration - customs unions - will be dealt with separately, using the EU as an example.